Captive [compact disc, unabridged] - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller., 2022)
Eve Duncan's daughter Jane now has everything she's dreamed of with her marriage to Seth Caleb and their newborn baby but their happily ever after is about to be upended in this gripping suspense novel from the number one best-selling author of The Persuasion. Fans were thrilled when Jane and Seth finally committed to a life together. Now we pick up where The Persuasion left off, and the couple is in Scotland with their newborn baby and her proud grandparents Eve Duncan and Joe Quinn. But a dark past follows Seth wherever he goes, and his newfound happiness is cruelly dashed by an evil psychopath. With Jane and the baby in danger, Seth will be stretched to the limits of his physical and emotional endurance while trying to save them in a fast-paced plot that leads to a stunning conclusion.